Optimizing the preparation of thin endometria in frozen-thawed embryo transfer: a retrospective cohort analysis - Ji, Xiaoxue; Wei, Chunxiao; Liu, Zhiru; Qiu, Lijun; Zhang, Jianwei (Frontiers in Endocrinology, 2025)
BackgroundTo date, there is no consensus on the optimal endometrial preparation protocol for frozen-thawed embryo transfer (FET) in patients with a thin endometrium. This study evaluated the effects of different endometrial preparation protocols on pregnancy outcomes in patients undergoing FET cycles.MethodsIn this retrospective cohort analysis, we included women with a thin endometrium who underwent FET cycles at the Department of Gynaecology, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, from January 1, 2015, to November 30, 2023. Based on the endometrial preparation protocols, the participants were divided into two groups: natural cycle (NC) and hormone replacement therapy (HRT). The primary outcomes measured were clinical pregnancy and live birth rates. Propensity score matching (PSM) was used to mitigate potential disparities between the groups. A comparative analysis of pregnancy outcomes was then performed between the groups.ResultsNo statistically significant differences were found in pregnancy outcomes between the two groups, even after applying PSM. However, patients with an endometrial thickness of ≤7 mm on the trigger day exhibited significantly higher rates of clinical and biochemical pregnancies when assigned to the HRT group.ConclusionsThe HRT protocol is advisable for FET cycles in patients with thin endometrium, particularly when the endometrial thickness is <7 mm on the day of hormonal trigger administration.